Smoking and inflammatory bowel disease. A case control study. Issue 3 (March 1988) - Lindberg, E; Tysk, C; Andersson, K; Järnerot, G
Abstract : A population case controlled study of smoking habits at the time of diagnosis was done in 260 patients with ulcerative colitis and 144 with Crohn's disease. Smokers had a decreased risk of acquiring ulcerative colitis in comparison with never smokers (relative risk 0.7) which appeared to be dose dependent. In former smokers a rebound effect was seen, especially in former heavy smokers, where the risk was sharply increased (relative risk 4.4). No sex difference was recorded. Smoking doubled the risk of acquiring Crohn's disease without any dose dependent pattern. In former smokers a non-significantly increased risk was observed. This might be caused by a carry over effect after stopping smoking, however, which possibly is reduced by time. No sex difference was seen.